AN ANALYSIS ON THE ATAMBUA STUDENTS’ MULTILINGUAL BACKGROUND AND THEIR ENGLISH ORAL PROFICIENCY - Graciela D Bete Do Nacimento, S.Pd (Fakultas Ilmu Budaya, Universitas Brawijaya, 2020)
Multilingualism is the ability of someone to operate more than one language for communication. Atambua people are multilingual since they have more than one language background, it make them difficult in speaking English. This study aims to Analyze the English Oral Proficiency (EOP) of the Atambua students with multilingual background.It is a descriptive qualitative research involving multilingual Atambua students who also speak English. 10 out of 200 as the researcher participants are selected through questionnaire develop by the researcher to know their multilingual background. EOP in form of monologue was employed to the students to know their level using scoring rubric by Brown (2001). Then, analysis was done to see the relation of their level of EOP with their number of language useand age of their English acquisition or learning.The result of this study showed that 2 students with 3 languages use have 3,0 and 3+ levels, (able to participate effectively in formal and informal situation, as well as the professional topics). 5 students with 4 languages use have various level, ranging 1+ (able to satisfy limited social demands) to the 3+ level. 1 student with 5 languages was in level 1+, and 2 students matering 6 languages were in level 1+ and level 2 (able to satisfy routine social demands). 2 students learned English before 10 year-old, and their EOP level was 3+. 8 other students learned English in their 11 up to 14 year-old. Interesting phenomenon found that only 1 out of 8 students with with 3 languages use get the highest level (3) even she learn English over golden age. It indicates that the result of the research is in line with the previous theory stated that multilingual person will face difficult in learning English, Bialystok( 2001).